The Effect of Hindlimb Studs on Movement Symmetry in Horses During Lungeing. (September 2014) - Sharp, H.; Pfau, T.; Hopkins, S.
Abstract : Reasons for performing study: Horseshoe studs are commonly used to increase traction between the foot and the ground in competition horses. Here we investigate the question of how hindlimb studs alter limb function by quantifying upper body kinematics during circular motion (lungeing). Objectives: This study quantified the effects of studs placed in the hind shoes on head and pelvic movement symmetry parameters commonly used for objective assessment of lameness. Study design: Prospective longitudinal interventional study. Methods: 15 horses were trotted on the straight and lunged on left and right circles on turf with/without a pair of studs in both hind shoes. Movement symmetry was assessed using inertial sensors mounted on poll, os sacrum and left and right tuber coxae. To eliminate the influence of the number of left/right asymmetrical horses in the sample, symmetry values were standardised to show left fore and/or right hind asymmetry on the straight. Differences in standardised head and pelvic symmetry index (SI) with and without studs were calculated and paired t tests were used to compare SI values with and without studs on the straight and on both reins. Results: Use of studs resulted in a significant difference (P = 0.02) in pelvic SI on the right lunge only but no difference for straight line and left lunge (both P>0.05). No significant difference was found for head movement symmetry (all P>0.05). Conclusions: Pelvic movement was altered with the 'weaker' right hindlimb (based on the calculation of standardised SI values) on the inside of the circle creating an increased 'hip hike'. In general, horses show increased limb angles and lower peak vertical force with the inside limb; our kinematic results show that this effect is exacerbated with studs. Future studies should investigate whether this 'intervention' is of diagnostic potential in sub‐clinically hindlimb lame horses. Acknowledgements: The authors would like to thank the owners and trainers whose horses were used in this study. Ethical animal research: The Royal Veterinary College Ethics and Welfare Committee approved this study and all procedures were performed with informed owner consent.Sources of funding: Funding was provided by The Royal Veterinary College for Harriet Sharp and Sophie Hopkins' research projects.Competing interests: None.